Pengaruh Kemampuan Akuntansi dan Budaya Organisasi terhadap Kinerja Perusahaan dengan SIA sebagai Variabel Moderasi - Euis Dayanti; Robiur Rahmat Putra (Politeknik Ganesha Medan, 2022)
The purpose of this study is to provide evidence on the impact and provide recommendations to companies on strategies to improve company performance. The research method used in this study is a quantitative method. The population in this study are employees who work in finance & accounting in Jabodetabek. The number of samples in this study were 282 respondents with data collection techniques using questionnaires. The data analysis technique used in this study uses structural equation modeling (SEM) with the help of PLS. The results of this study prove that accounting ability has a significant and significant effect on company performance, organizational culture has a significant and significant effect on company performance, accounting information systems have a significant and significant effect on company performance, and accounting information systems influence/capable of moderating accounting capabilities and organizational culture on company performance. The implication of this research is to recommend to companies related to efforts to improve company performance by paying more attention to accounting capabilities, organizational culture and accounting information systems. The role of the Accounting Information System here is very large, because seeing its large role it directly affects the company's performance and at the same time is able to moderate accounting capabilities and organizational culture on company performance. In addition, the company must propose strategic methods such as providing a good and adequate accounting information system, education, training, and motivation for employees in supporting the work of course this is also a strategic way to improve company performance.